Cross-Platform Personal Life Management App Using Data Analytics - Mohana, Muniandy; Heng, Alex Kong Yew (INTI International University, 2019)
Personal life management apps are needed to solve problems relate to poor productivity and procrastination by managing an individual’s life in a day-to-day basis with reminders, to-do lists and habit tracking functions. The problem is, these apps are available separately and it may be costly to build one app across multiple platforms. Having a single personal life management app would save time, reduce stress, build user’s confidence and help user get things done. This app would be essential in helping people keep their life on track and continue to improving themselves further. The proposed system is a cross-platform app that has features of to-do list, calendar and simple analytics